Onset of Labor in Post-Term Pregnancy by Chamomile - Gholami, Fereshte (Iran Red Crescent Med J, 2016)
BACKGROUND: Post-term pregnancy is an important factor in perinatal mortality and morbidity. Generally, to reduce perinatal mortality in pregnancy, the delivery is done before adverse perinatal morbidity occurs. To prevent prolonged pregnancy, labor is induced with chemical drugs and complementary therapies. Due to the side effects and contraindications of chemical medicine, the use of herbs has been investigated in the induction of labor in post-term pregnancy. OBJECTIVES: This study was done to identify the effect of chamomile on inducing labor in women with post-term pregnancy of Shahid Akbarabadi hospital in Tehran in 2013. PATIENTS AND METHODS: This double-blind clinical trial study was performed in Iran on 80 post-term pregnant women with a gestational age of 40 weeks or more, a single pregnancy, 18 - 35 years old, cephalic presentation, an estimated fetal weight of 2500 - 4000 grams, an absence of uterine contraction, a cervical Bishop score of less than 4, the safety of the membrane, and low-risk pregnancy; they were randomly assigned to one of two groups of 40 women. Each of the participants was given a bottle containing 42 capsules (500 mg each) and took 2 capsules every 8 hours. The data were collected through the questionnaire of demographic observational, and examinal characteristics. Descriptive statistics, independent samples t-test, and Fisher’s exact test using SPSS (16/win) were used to determine and compare the effects of drugs on inducing labor in the groups. RESULTS: After a week of using the first dose, the results showed that in 92.5% of the chamomile group and 62.5% in the placebo group, delivery symptoms started after taking the oral capsules, and there were significant statistical differences between the two groups for the onset of labor (P = 0.003) There was a noticeable statistical difference between the two groups regarding the mean interval time to the onset of labor pain after taking the capsules (P = 0.000). CONCLUSIONS: In this study¸ chamomile stimulated labor in post-term pregnancy. With further studies, chamomile, which has no chemical side effects, can be suggested for stimulating labor in post-term pregnancy.